Is repeat sentinel lymph node biopsy possible for surgical axillary staging among patients with ipsilateral breast tumor recurrence?. Issue 10 (19th February 2023) - Lu, Xunxi; He, Mengting; Yu, Luoting; Gou, Zongchao
Abstract: Background: There is a lack of studies assessing the survival of repeat sentinel lymph node biopsy (rSLNB) versus axillary lymph node dissection (ALND) for surgical axillary staging among patients with ipsilateral breast tumor recurrence (IBTR). Methods: We retrospectively identified patients with IBTR from the Surveillance, Epidemiology, and End Results database from 2000 to 2017. The primary outcome was overall survival (OS) between the rSLNB and ALND groups. Results: Of the 2141 women with IBTR after lumpectomy and SLNB, 524 did not receive surgical axillary staging (nonsurgery group) and 1617 patients who did undergo axilla surgery received either rSLNB or ALND as axillary staging (1268 with rSLNB and 349 with ALND). The 10‐year OS rates were 61.9% for the nonsurgery and 73.8% for axilla surgery groups ( p  = .001). In the 1:1 matched cohorts, the 10‐year OS rates were 61.4% for the nonsurgery and 69.1% for axilla surgery groups ( p  = .072). After adjusting for other factors, axillary surgery treatment of IBTR was an independent favorable factor for OS (hazard ratio [HR], 0.71; 95% CI, 0.56–0.90; p  = .004). Within the axilla surgery group, rSLNB presented a comparable 10‐year OS to the ALND cohort (log‐rank test p  = .054). Multivariate Cox analysis, as well as subgroup analysis, showed that rSLNB had a similar benefit to ALND (10‐year OS; HR, 1.18; 95% CI, 0.88–1.58; p  = .268). Conclusions: The results of this cohort study suggested that receiving surgical axillary staging was associated with better survival of IBTR patients, and rSLNB had a similar long‐term survival outcome as ALND. rSLNB might be considered for surgical axillary staging among patients with IBTR after lumpectomy and initial SLNB. Abstract : This study suggested that receiving surgical axillary staging was associated with better survival of patients with ipsilateral breast tumor recurrence (IBTR), and repeat sentinel lymph node biopsy (rSLNB) had a similar long‐term survival outcome as axillary lymph node dissection. The importance of this finding is that rSLNB might be considered for surgical axillary staging among patients with IBTR after lumpectomy and initial SLNB.